2000
DOI: 10.1016/s0921-5107(99)00555-3
|View full text |Cite
|
Sign up to set email alerts
|

Complete and absolute photonic bandgaps in highly symmetric photonic quasicrystals embedded in low refractive index materials

Abstract: It is firmly established that periodic lattice structures can support photonic bandgaps (PBG). However, complete and absolute photonic bandgaps (CAPBG) have only been achieved in high dielectric constant mediums such as GaAs (m = 13.6). An artificial quasiperiodic photonic crystal based on the random square-triangle tiling system was designed and fabricated. The photonic quasicrystal possesses 12-fold symmetry and was analysed using a finite difference time domain (FDTD) approach. High orders of symmetry in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Since ordered periodicities are not involved, these structures do not carry the usual geometrical constraints associated with periodic crystallographic restrictions. Quasi-ordered photonic crystal geometries therefore create a more isotropic optical scattering structure due to their relatively spherical Brillouin zone boundaries [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since ordered periodicities are not involved, these structures do not carry the usual geometrical constraints associated with periodic crystallographic restrictions. Quasi-ordered photonic crystal geometries therefore create a more isotropic optical scattering structure due to their relatively spherical Brillouin zone boundaries [6].…”
Section: Resultsmentioning
confidence: 99%
“…Where quasi-ordered PCs have been synthetically fabricated [6,7] their design has been limited to systems with no more than 12-fold rotational symmetry. This has only marginally reduced the requirement for use of such ultra-high index materials to create the FCPBG properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two-dimensional photonic crystals, there have been attempts to enhance the band gap response by using quasi-crystals [21,22]. These have exploited a periodic tiling such as Penrose tiling [23] as well as an inverse Fourier transform approach, and up to 18-fold symmetric structures have been obtained [24].…”
Section: Low Index Contrast Photonic Structuresmentioning
confidence: 99%
“…2D photonic quasicrystals are structures possessing an aperiodic modulation of the relative permittivity with long-range order based upon quasicrystalline tilings, and they can be constructed by decorating the quasiperiodic tiling with the usual dielectric rods or cylinders. Several experimental and theoretical studies have shown evidence of 2D PBGs, accompanied by dips in the transmission spectrum, in different photonic structures based on quasicrystalline geometries [6][7][8][9][10][11][12][13][14][15]. Further, these studies have found that the band gap formed from photonic quasicrystals is due to the shortrange quasicrystalline structure and not due to the periodicity enforced by the boundary conditions of calculations based on a supercell approach [8].…”
Section: Introductionmentioning
confidence: 99%